Effectiveness of national and subnational infection prevention and control interventions in high-income and upper-middle-income countries: a systematic review. Issue 5 (May 2018) - Price, Lesley; MacDonald, Jennifer; Melone, Lynn; Howe, Tracey; Flowers, Paul; Currie, Kay; Curran, Evonne; Ness, Valerie; Waddell, Debbie; Manoukian, Sarkis; McFarland, Agi; Kilpatrick, Claire; et al.
Summary: Evidence-based guidance for national infection prevention and control (IPC) programmes is needed to support national and global capacity building to reduce health-care-associated infection and antimicrobial resistance. In this systematic review we investigate evidence on the effectiveness of IPC interventions implemented at national or subnational levels to inform the development of WHO guidelines on the core components of national IPC programmes. We searched CENTRAL, CINAHL, Embase, MEDLINE, and WHO IRIS databases for publications between Jan 1, 2000, and April 19, 2017. 29 studies that met the eligibility criteria (ie, economic evaluations, cluster-randomised trials, non-randomised trials, controlled before-and-after studies, and interrupted time-series studies exploring the effective of these interventions) were categorised according to intervention type: multimodal, care bundles, policies, and surveillance, monitoring, and feedback. Evidence of effectiveness was found in all categories but the best quality evidence was on multimodal interventions and surveillance, monitoring, and feedback. We call for improvements in study design, reporting of research, and quality of evidence particularly from low-income countries, to strengthen the uptake and international relevance of IPC interventions.